An Updated View of Cisplatin Transport. Issue 15 (27th March 2013) - Arnesano, Fabio; Losacco, Maurizio; Natile, Giovanni
Abstract: Cisplatin, or cis ‐diamminedichloridoplatinum(II) cis ‐[PtCl2 (NH3 )2 ], is a platinum‐based anticancer drug largely used for the treatment of various types of cancers, including ovarian and colorectal carcinomas, sarcomas, and lymphomas. Together with other platinum‐based drugs, it triggers malignant cell death by binding to nuclear DNA, which appears to be the ultimate target. In addition to passive diffusion across the cell membrane, other transport mechanisms, including endocytosis and some active or facilitated transport, are currently proposed to play a pivotal role in the uptake of platinum‐based drugs. In this microreview, we will give an updated view of the current literature regarding cisplatin transport and processing inside the cell, with special emphasis on the membrane copper transporter Ctr1 and the soluble copper chaperone Atox1. Abstract : Membrane transporters and soluble chaperones of copper ions mediate cellular uptake of and resistance to platinum‐based drugs. In this microreview, the interactions of cisplatin with the methionine‐rich motifs of the copper permease Ctr1 and with the cysteine motifs of the cytosolic copper chaperone Atox1 are described. Only in the latter case does the drug retain its ammine ligands essential for antitumor activity.